Inteligencia emocional y rendimiento académico en matemática de estudiantes del cuarto y quinto de secundaria de una institución parroquial de Ventanilla - Palomino Sinchi, Germán Roger (2010)
This research studies the relationship between emotional intelligence and academic achievement in mathematics in 4th and 5th year of secondary students in a parish School district Ventanilla. In total, 50 students, 20 men and 30 women ranging from 15 to 17 years, who completed the Inventory of Emotional Intelligence Bar-On Ice, adapted by Nelly Ugarriza in a sample taken in Lima, correlating with the record of scores in Mathematics. The results describe the positive relationship between these two variables. There was also a positive relationship among emotional intelligence, Intrapersonal components and general mood in Academic Performance.